Proceedings of the Workshop on Stylistic Variation 2017
DOI: 10.18653/v1/w17-4912
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Linguistic Style Aspects in Neural Language Generation

Abstract: Most work on neural natural language generation (NNLG) focus on controlling the content of the generated text. We experiment with controlling several stylistic aspects of the generated text, in addition to its content. The method is based on conditioned RNN language model, where the desired content as well as the stylistic parameters serve as conditioning contexts. We demonstrate the approach on the movie reviews domain and show that it is successful in generating coherent sentences corresponding to the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
222
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(222 citation statements)
references
References 25 publications
0
222
0
Order By: Relevance
“…Content coupledness means how much style is tightly or loosely coupled to the content of original text. Ficler and Goldberg (2017) controlled different styles (e.g., descriptive, professional) in text variation, regardless of its coupledness to the semantics of text. However, it is often observed that content words are tightly coupled with its styles (Kang et al, 2019;Preoţiuc-Pietro and Ungar, 2018).…”
Section: Categorization Of Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…Content coupledness means how much style is tightly or loosely coupled to the content of original text. Ficler and Goldberg (2017) controlled different styles (e.g., descriptive, professional) in text variation, regardless of its coupledness to the semantics of text. However, it is often observed that content words are tightly coupled with its styles (Kang et al, 2019;Preoţiuc-Pietro and Ungar, 2018).…”
Section: Categorization Of Stylesmentioning
confidence: 99%
“…More severe semantic drift. The biggest challenge in collecting cross-style dataset (Kang et al, 2019) or controlling multiple styles in generation (Ficler and Goldberg, 2017) is to diversify style of text but at the same time preserve the meaning, in order to avoid semantic drift. It can be addressed by collecting text in parallel or preserving the meaning using various techniques.…”
Section: Challengesmentioning
confidence: 99%
“…In each of these cases, the diversity in outputs is quite small given the constraints of the meaning representation, style is often constrained to interjections (like "yeah"), and there is no original style from which to transfer. Ficler and Goldberg (2017) investigate using stylistic parameters and content parameters to control text generation using a movie review dataset. Their stylistic parameters are created using wordlevel heuristics and they are successful in controlling these parameters in the outputs.…”
Section: Controlling Linguistic Featuresmentioning
confidence: 99%
“…We consider the problem of automatic story continuation generation, i.e., how to generate story continuations conditioned on the story context. Inspired by recent work in controllable generation (Hu et al, 2017;Ficler and Goldberg, 2017), we propose a simple and effective modeling framework for controlled generation of multiple, diverse outputs based on interpretable control variables. Each control variable corresponds to an attribute of a sentence.…”
Section: Introductionmentioning
confidence: 99%